COMPARATIVE ANALYSIS OF ISLAMIC BANK PERFORMANCE BASED ON RGEC AND ISLAMICITY PERFORMANCE INDEX - Darwis Harahap; Rini Hayati Lubis; Siti Ena Aisyah Simbolon; Ferri Alfadri (IAIN Batusangkar, 2022)
Comparative Analysis of Islamic Bank Performance Based on RGEC and Islamicity Performance Index. The increase in Islamic banking makes Islamic banks must be able to maintain their performance in order to survive. The performance of Islamic banks can be measured using the CAMELS method until 2013, but after the issuance of PBI Number 13/1/PBI/2011 and POJK Number 8/POJK.03/2014 regarding the assessment of the soundness of Islamic banks, Islamic banks used the RGEC method. However, the RGEC method is not able to reveal the social function of a bank. Meanwhile, Islamic banks need a measuring instrument that is able to reveal the social function of the bank. So this research uses the Islamicity Performance Index method. Therefore, the problem in the research is how to compare the performance of PT. Bank Muamalat Indonesia Tbk and PT. Bank Syariah Mandiri Tbk based on RGEC and Islamicity Performance Index. The population in this study is the financial performance report data of PT. Bank Muamalat Indonesia Tbk and PT. Bank Syariah Mandiri Tbk in 2016-2020. The samples in this study are financial ratios, namely NPF, FDR, GCG, ROA, CAR, PSR, ZPR, EDR, IIR, and IsIR. Meanwhile, the data analysis technique used independent sample t-test and Mann Whitney test. The result of this research is the performance of PT. Bank Syariah Mandiri Tbk is better than the performance of PT. Bank Muamalat Indonesia Tbk.